Formation of a supramolecular charge-transfer complex. Ultrafast excited state dynamics and quantum-chemical calculations. Issue 1 (21st November 2018) - Volchkov, Valery V.; Khimich, Mikhail N.; Rusalov, Mikhail V.; Gostev, Fedor E.; Shelaev, Ivan V.; Nadtochenko, Viktor A.; Vedernikov, Artem I.; Gromov, Sergey P.; Freidzon, Alexandra Ya.; Alfimov, Michael V.; Melnikov, Mikhail Ya.
Abstract : The relaxation scheme of the1·3 singlet state excited by a 25 fs laser pulse was proposed. It includes very fast vibrational relaxation, and direct and back electron transfer resulting in complete fluorescence quenching. Abstract : The formation of a supramolecular complex of bis(18-crown-6)stilbene (1 ) and 4, 4′-bipyridine with two ammoniopropyl N -substituents (3 ) and the substitution reaction between1·3 and alkali and alkaline-earth metal perchlorates have been studied using absorption, steady-state fluorescence, and femtosecond transient absorption spectroscopy. The formation of1 ·(M n + )2 complexes in acetonitrile was demonstrated. The weak long-wavelength charge-transfer absorption band of1·3 completely vanishes upon complexation with metal cations because of disruption of the pseudocyclic structure. The spectroscopic and luminescence parameters, stability and substitution constants were calculated. The relaxation scheme of the1·3 singlet state excited by a 25 fs laser pulse was proposed. It includes very fast vibrational relaxation and direct ( τ CT-d = 0.32 ps) and back ( τ CT-b = 0.51 ps) electron transfer resulting in complete fluorescence quenching. The quantum-chemistry calculations revealed the species taking part in the ET process and elucidated the mechanism of relaxation of the excited complex.